Visual Internal Urethrotomy for Adult Male Urethral Stricture Has Poor Long-Term Results - Waleed Al Taweel; Raouf Seyam (Advances in Urology)
Objective. To determine the long-term stricture-free rate after visual internal urethrotomy following initial and follow-up urethrotomies. Methods. The records of all male patients who underwent direct visual internal urethrotomy for urethral stricture disease in our hospital between July 2004 and May 2012 were reviewed. The Kaplan-Meier method was used to analyze stricture-free probability after the first, second, third, fourth, and fifth urethrotomies. Results. A total of 301 patients were included. The overall stricture-free rate at the 36-month follow-up was 8.3% with a median time to recurrence of 10 months (95% CI of 9.5 to 10.5, range: 2–36). The stricture-free rate after one urethrotomy was 12.1% with a median time to recurrence of eight months (95% CI of 7.1–8.9). After the second urethrotomy, the stricture-free rate was 7.9% with a median time to recurrence of 10 months (95% CI of 9.3 to 10.6). After the third to fifth procedures, the stricture-free rate was 0%. There was no significant difference in the stricture-free rate between single and multiple procedures. Conclusion. The long-term stricture-free rate of visual internal urethrotomy is modest even after a single procedure.